Neuropsychological and Social Factors of Deviant Behaviour in Adolescents - Gut Y.N; Kabardov M.K (Moscow State University of Psychology and Education, 2018)
The paper focuses on factors influencing deviant behaviour in adolescents and presents outcomes of a study that involved 60 adolescents from a youth detention center and 60 school students aged 15 years. Functional asymmetry of the brain is one of the key integrative features in the brain organization that plays an important role in personality development and, for instance, in the development of personality traits associated with delinquency. We explored time perspective and personality traits of the adolescent subjects as well as their inclination towards various forms of deviant behaviour and the levels of neurotisation and psychopathisation and found significant correlations between deviant behavior and personality traits determined by functional brain asymmetry. As we show, the specifics of the lateral organization of mental processes determines the specifics of time orientation in the adolescents, which, in turn, affects the individual's behavioural regulation in situations of social orientation and promotes either socially accepted or deviant behaviour.Such studies open up possibilities for a better understanding of deviant behaviour as well as for its prevention and early interventions.